Guinea-Bissau : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Financing Assurances Review; Staff Report; Informational Annex; Press Release on the Review. (IMF Staff Country Reports; Country Report, 2011)
The review highlights that the government of Guinea-Bissau maintained macroeconomic stability under challenging circumstances. The government implemented satisfactory policies under the IMF supported program even in severe conditions. The authorities have met all performance criteria and all structural reforms for the second review. Sound macroeconomic policies, strengthened institutions, and debt relief have stabilized the economy and supported confidence building. It is critical that the government maintain the reform momentum and continue to build on the satisfactory performance under the Extended Credit Facility (ECF).